How do you want me? The impact of photographic communication in the social representation of animals - Guarino, Francesca (Community Notebook. People, Education and Welfare in the Society 5.0, 2024)
Depicting animals, photographing them, and exhibiting them on social media platforms requires defining narrative lines that today can hardly be considered neutral or "natural". This article addresses the social representation of animals through a detailed reflection primarily focused on photographic discourse, whether static or moving, from traditional media to new media. It includes examples of constructing and deconstructing social imagery and interpretative porosity.